Sea Urchen (Echinoidea) Diversity in the Coastal Area at Mawasangka District, Central Buton Regency - Maretik Maretik; Yanti Yanti; Fitrianti Handayani (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
Sea urchins are marine invertebrates that are grouped in the Echinoidea class and Echinodermataphylum. Mawasangka is a district that has a large coastal area with a fairly good seagrass and coral reef ecosystem that plays an important role in the life cycle process of marine organisms, for instant as a habitat and food source for sea urchins. However, until now, information about the diversity of sea urchins in the coastal areas in Mawasangka District has not been reported. Thus, this research is very important. This research began with a location survey, field observation, and sampling. Supporting data such as temperature, pH, brightness, depth and salinity were also measured. The results showed that the number of species in 3 research locations in the coastal area of Mawasangka District was 5 species, consisting of 3 species from the genus Diadema, namely Diadema cytosum, Diadema antillarium, and Diadema savignyi, and 2 species from the Echinotrix genus, namely Echinothrix calamaris and Echinothrix diadema. The highest number of species diversity was found on the Pasi Kobungi beach. This happened because the habitat and environmental conditions at Pasi Kobungi Beach were very compatible for 5 species found. The species with the greatest abundance was sea urchins from the species of Diadema cytosum. It was found out that the coral reef substrate and seagrass in three research locations were important habitats for the growth of Diadema setosum and were easy to adapt to the environment. Due to the abundance of sea urchins from the Diadema cytosum species as well as many benefits of it for the environment, it can be concluded that the condition of the coastal area of Mawasangka District is still classified as healthy and well preserved.